Reference values for spirometry in preschool children - Edjane F. Burity; Carlos A.C. Pereira; José A. Rizzo; Murilo C.A. Brito; Emanuel S.C. Sarinho (Brazilian Society of Pediatrics, 2013)
Objectives: Reference values for lung function tests differ in samples from different countries, including values for preschoolers. The main objective of this study was to derive reference values in this population. Methods: A prospective study was conducted through a questionnaire applied to 425 preschool children aged 3 to 6 years, from schools and day-care centers in a metropolitan city in Brazil. Children were selected by simple random sampling from the aforementioned schools. Peak expiratory flow (PEF), forced vital capacity (FVC), forced expiratory volumes (FEV1, FEV0.50), forced expiratory flow (FEF25-75) and FEV1/FVC, FEV0.5/FVC and FEF25-75/FVC ratios were evaluated. Results: Of the 425 children enrolled, 321 (75.6%) underwent the tests. Of these, 135 (42.0%) showed acceptable results with full expiratory curves and thus were included in the regression analysis to define the reference values. Height and gender significantly influenced FVC values through linear and logarithmic regression analysis. In males, R2 increased with the logarithmic model for FVC and FEV, but the linear model was retained for its simplicity. The lower limits were calculated by measuring the fifth percentile residues. Conclusion: Full expiratory curves are more difficult to obtain in preschoolers. In addition to height, gender also influences the measures of FVC and FEV. Reference values were defined for spirometry in preschool children in this population, which are applicable to similar populations.